Visible on-site detection of Ara h 1 by the switchable-linker-mediated precipitation of gold nanoparticles. (1st August 2021) - Kim, Eunghee; Hahn, Jungwoo; Ban, Choongjin; Jo, Youngje; Han, Hyebin; Lim, Seokwon; Choi, Young Jin
Highlights: Switchable linker (SL)-based assay could detect Ara h 1 in the field. The SL was switched off by Ara h 1, which generated a visual signal. Ara h 1 in 0.19 mg of peanut protein per 30 g of cookie was detectable. Total assay time was less than 60 min, without the use of analytical equipment. Abstract: Biosensors have been widely applied in tests for allergens, but on-site detection remains a challenge. Herein, we proposed a detection procedure for peanut Ara h 1 as a representative allergen, which was extracted from a cookie, thereby minimising the need for any complex pretreatment that was difficult to perform, and enabling the visual detection of the target without the use of analytical equipment. The extraction procedure was performed in less than 30 min using a syringe and filter (0.45 μm). The detection method for Ara h 1 was based on the aggregation of switchable linkers (SL) and gold nanoparticles (AuNP), and the presence of 0.19 mg peanut protein per 30 g of cookie could be confirmed within 30 min based on the AuNP/SL concentration ratio by the precipitation. This proposed procedure could be successfully applied to the detection of a wide range of food allergens.